Differing Patterns of Liver Disease Progression and Hepatitis C Virus (HCV) Quasispecies Evolution in Children Vertically Coinfected with HCV and Human Immunodeficiency Virus Type 1 - Canobio, Sophie (American Society for Microbiology, 2004)
Hepatitis C virus (HCV) quasispeciation was studied in two children vertically coinfected with HCV and human immunodeficiency virus type 1 (HIV-1). HCV quasispecies diversification and liver injury were more significant in patient C1, who was immunocompetent with anti-HIV therapy, than in patient C2, who was immunosuppressed, in consistency with modulation of HCV quasispeciation and liver injury by immunocompetence in coinfected children.